Effective or Impractical? Discussing Students' Perceptions toward Learning Management Systems in English Language Learning - Aminah Suriaman; Konder Manurung; Mukrim Mukrim; Aisah Apridayani; Agussatriana Agussatriana (Universitas Negeri Makassar, 2023)
Learning Management System (LMS) platform is currently popularly used by universities or institutions as an e-learning platform based. Currently, it may be utilized successfully as a platform to engage students in a classroom context. This study aims to determine the use of the learning management system (LMS) in English language learning based on the analysis of students' perceptions and to establish whether the platforms used contributed to the learning goals in the English Department at Tadulako University. The research design utilizes the descriptive qualitative research method. The finding of the study indicated that learners expressed both sides of the usage of the LMS platform in English language learning; effective and impractical perception. It is effective because the LMS platform improved their comprehension, promoted independent learning, inspired students to complete all tasks and quizzes, and eventually allowed students to achieve good learning outcomes. Meanwhile, for impractical usage, the LMS platform has network instability and limited opportunity for real-time discussion and gets immediate feedback from lecturers. However, the benefits of the LMS platform outweigh its drawbacks.